ANALISIS KEPADATAN SUBGRADE APRON HANGGAR-D BALAI KALIBRASI FASILITAS PENERBANGAN - Sukamto; Kusumastuti Rahmawati (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
Apron needs a subgrade with a certain density in order to meet the requirements of aircraft ACN. Subgrade from the ground requires special attention because it is potential to cause a decrease (consolidation) if it does not get adequate compaction process. Subgrade soil density needs to be tested first before undergoing subsequent construction process. Density test can be done by means of the Dynamic Cone Penetrometer ((DCP). Value of CBR is obtained by correlating the number of tool collisions with the depth of conus penetration. Subgrade soil density test is done in the apron construction area of hangar-D Curug Calibration Center for Flight Facilities